(untitled) (Actualizaciones en Sida e Infectología, 2023)
We are in the first months of 2023 and we have not yet been able to declare the end of the pandemic that began more than three years ago, leaving a toll not only of millions of deaths but also of economic, psychological and social damage that will take a long time to repair. Nature, moreover, is relentless and is increasingly exposing us to new emerging virus threats with pandemic potential. Now it is the turn of Avian influenza (a.k.a. bird flu) and we ask ourselves: What do we know? What is happening? How can we prevent it? What do we know? Avian influenza is an infectious disease that mainly affects birds. It is caused by a type “A” Influenza virus of the Orthomyxoviridae family. Avian Influenza A (AIA) viruses can be classified into two groups in relation to their capacity to cause disease and death in birds: low or high pathogenicity. Those of low pathogenicity usually cause mild disease, while those of high pathogenicity -mainly H5 and H7 subtypes- can cause severe disease that can spread rapidly, with high mortality rates in different bird species1. The most common way for the virus to enter a territory is through migratory birds. It affects different types of wild and domestic birds. Poultry are very susceptible to the disease and may die in large numbers, generating great economic losses. Waterfowl represent an important reservoir. They can carry the disease without showing any symptoms. Influenza viruses in these reservoirs show limited evolution, with subtle minor antigenic changes, the result of which usually does not modify the way the virus affects its host. Only when they spread to other species do major antigenic changes occur, resulting in new variants that pose potential threats to human and animal health2. For this reason, reports of sporadic AIA virus infections in various mammals, such as foxes, dogs, cats, tigers, leopards, bears, minks and sea lions, are cause for concern3. Most influenza viruses circulating in birds are not zoonotic and have a restricted ability to infect humans. However, some highly pathogenic strains of AIA can do so, generating clinical pictures that can vary from mild to severe forms, including death1. The main risk factor for transmission from birds to humans is direct or indirect contact with infected animals or with environments and surfaces contaminated by secretions or excretions. The disease is not transmitted to humans through the consumption of avian meat and its by-products4. To date, no sustained human-to-human transmission of AIA virus has been reported. What is happening? On February 15, 2023, the Argentine National Agrifood Health and Quality Service (SENASA) reported the first local detection of H5N1 AIA in wild birds in the Pozuelos lagoon, in the northwest of the province of Jujuy, near the border with Bolivia4. Since then, multiple outbreaks have been reported in different provinces affecting not only wild and backyard birds but also birds in the commercial sector. At the moment, no human cases have been reported in our country. H5N1 AIA viruses first appeared in China in 1996. They caused large outbreaks in poultry in Hong Kong in 1997, resulting in 18 human infections. The outbreak was controlled, but the virus was not eradicated in birds and reappeared in 2003 to spread in Asia, Africa, Europe and the Middle East, causing outbreaks in poultry and sporadic human infections5. In 2014, the virus was identified for the first time in birds in the Americas region (North America). Between 2021 and 2022, Europe and North America recorded their largest and most widespread outbreak, with unusual persistence of the virus in wild bird populations. As of March 13, 2023, 16 countries in the Americas region detected outbreaks in poultry, poultry farms and/ or wild birds, and mammals (Table 1)6. Regarding human cases of H5N1 AIA infection, from 2003 to January 2023, a total of 868 cases with 457 deaths (case fatality rate 53%) were reported worldwide. In the Americas region, the first case was reported in the United States in April 2022. Subsequently, in January 2023, the first case in the Latin America and Caribbean region was reported in Ecuador6. How can we prevent it? SENASA, within the framework of the sanitary emergency declared throughout the national territory, emphasizes the importance of notifying the finding of dead birds or birds with nervous, respiratory and/or digestive symptoms and of reinforcing biosecurity in farms in order to prevent the entry of the virus and its spread7. Prevention measures for the productive sector as well as for backyard poultry keepers and tourists include frequent hand washing, avoiding direct contact with contaminated birds or surfaces, preventing contact between domestic birds and wild birds, wearing appropriate clothing and checking the health of the birds, among others. Commentary Although for the time being the current outbreak represents a threat to animal health and poultry production, the persistence and extension of the outbreak leads to increased human contact with infected animals or contaminated environments, thus becoming a threat to human health as well. We cannot predict when the next influenza pandemic will occur or which virus will cause it. We have learned from previous pandemics that the origin of the pandemic influenza virus was the result of a combination of human, swine and avian influenza virus genes. We are facing the largest outbreak of H5N1 AIA ever recorded in the Americas region. Overcoming this challenge requires multidisciplinary work to coordinate surveillance, prevention and control activities to minimize the impact on animal, human and environmental health.